Digital Humanities: Community Participation in the Balinese Language Digital Dictionary - Cokorda Cokorda; IB Ary Indra Iswara; I Komang Ari Mogi (Jurnal Sistem Informasi, 2020)
In recent years, the capability of Balinese people to write and speak their mother tongue has declined significantly among the younger generations because of the growing influence and adoption of the national language, Bahasa Indonesia. It has spread rapidly among Balinese youth because it is considerably more straightforward than the Balinese language and is free of caste regulations. In this paper, we present the details of our digital humanities preservation research dealing with the Balinese language. We utilize community-based crowdsourcing to participate in expanding and enriching the BASABali Wiki digital dictionary in the form of an online competition. Ninety-six participants in 24 groups participated in our study, and their contribution populated 2686 new unique sentences to the BASABali Wiki digital dictionary. We also discuss the procedures employed to evaluate the digital dictionary: to receive feedback on the digital dictionary system and our approach to acquiring the knowledge of the community.